PENGARUH EDUKASI GIZI MELALUI MEDIA INTERACTIVE BOOK TERHADAP PENGETAHUAN DAN SIKAP TENTANG MAKANAN SEHAT PADA ANAK UMUR 9-12 TAHUN - Safira Rizki Amalia; Vitria Melani; Laras Sitoayu; Yulia Wahyuni (ARGIPA (Arsip Gizi dan Pangan), 2023)
School-age children often do not pay attention to the quality and quantity of their food consumption. Therefore, nutrition education about healthy food is needed to increase their knowledge and attitudes in choosing healthy food to support their growth and development. This study aimed to analyze the effect of nutrition education through the media "Interactive Book" on knowledge and attitudes about healthy food in children aged 9-12 years. This research was conducted in several areas in Serang City, Banten. A quasi-experimental was designed with one group pretest-posttest. The subjects of this study used 35 children. Data analysis used paired sample t-test. The results showed there was an increase in knowledge and attitude scores after being given education with interactive book media (post-test 1). In posttest 2 there was a slight decrease in the average score, but both were still in the good category. The results of the paired t-test analysis showed that there was a significant difference in knowledge and attitude scores between before and after being given education. Interactive book media is proven to increase the knowledge and attitudes of school-age children. This media can be used as an effective nutrition education media for school children aged 9-12 years